Corrosion resistance and biological properties of a micro–nano structured Ti surface consisting of TiO2 and hydroxyapatite. Issue 53 (30th June 2017) - Hao, Jingzu; Li, Ying; Wang, Xiaolin; Zhang, Xianlin; Li, Baoe; Li, Haipeng; Zhou, Linxi; Yin, Fuxing; Liang, Chunyong; Wang, Hongshui
Abstract : A micro–nanostructured Ti surface consisting of TiO2 and HA was prepared by MAO, and showed improved corrosion resistance and biological properties. Abstract : A micro–nano structured titanium (Ti) surface consisting of titania (TiO2 ) and hydroxyapatite (HA) was produced by one-step micro-arc oxidation (MAO) to improve the corrosion resistance and biological properties. The corrosion resistance was evaluated in simulated body fluids (SBF) by electrochemical impedance spectroscopy (EIS) and anodic polarisation tests. The biological properties were investigated by in vitro cell co-culture experiments and in vivo experiments. The results showed that a microstructured TiO2 coating loaded with a nanostructured HA slice could be obtained on the Ti substrate during the MAO process. The MAO induced composite coating showed an increased resistance value and corrosion potential. It also promoted the cell behaviors (proliferation and spreading) on the Ti surface. After implantation in the rat tibias, the bonding strength between the bone tissues and implant was enhanced. The improved corrosion resistance was attributed to the increased thickness of the oxide layer, and the enhanced biological properties resulted from the micro–nanostructure and HA on the Ti surface. Based on these results, it was concluded that the micro–nano structured Ti surface consisting of TiO2 and HA prepared by MAO has great potential to be applied in the clinic.